Electroporation-Based CRISPR/Cas9 Mosaic Mutagenesis of β-Tubulin in the Cultured Oyster - Jiulin Chan; Jiulin Chan; Wei Zhang; Wei Zhang; Wei Zhang; Yue Xu; Yue Xu; Yu Xue; Yu Xue; Yu Xue; Linlin Zhang; Linlin Zhang; et al. (Frontiers in Marine Science, 2022)
Genome editing using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 is enabling genetics improvement of productive traits in aquaculture. Previous studies have proven CRISPR/Cas9 to be feasible in oyster, one of the most cultured shellfish species. Here, we applied electroporation-based CRISPR/Cas9 knockout of β-tubulin and built a highly efficient genome editing system in Crassostrea gigas angulate. We identified the β-tubulin gene in the oyster genome and showed its spatiotemporal expression patterns by analyzing RNA-seq data and larval in situ hybridization. We further designed multiple highly specific guide RNAs (sgRNAs) for its coding sequences. Long fragment deletions were detected in the mutants by agarose gel electrophoresis screening and further verified by Sanger sequencing. In addition, the expression patterns of Cgβ-tubulin in the trochophore peritroch and intestinal cilia cells were altered in the mutants. Scanning electron microscopy represented shortened and almost complete depleted cilia at the positions of peritroch and the posterior cilium ring in Cgβ-tubulin mosaic knockout trochophores. Moreover, the larval swimming behavior in the mutants was detected to be significantly decreased by motility assay. These results demonstrate that β-tubulin is sufficient to mediate cilia development and swimming behavior in oyster larvae. By applying Cgβ-tubulin as a marker gene, our study established CRISPR/Cas9-mediated mosaic mutagenesis technology based on electroporation, providing an efficient tool for gene function validation in the oyster. Moreover, our research also set up an example that can be used in genetic engineering breeding and productive traits improvement in oysters and other aquaculture species.